Psychological support of psychology students’ professional formation - Elena А. Denisova; Irina V. Kostakova; Sergei А. Kuz'michev (Российский психологический журнал, 2018)
Introduction. The article discusses the problem of psychological support of psychology students’ professional formation on example of Togliatti State University students. The system approach in current domestic research considers professional formation as a process and integral phenomenon of mutual influence of a human and professional activity.